An information retrieval system for Quranic texts: a proposed system design - Noordin, Mohamad Fauzan; Othman, Roslina (2006)
This project proposed a system design for retrieving Quranic texts and any knowledge that derived or cites al-Quran. The objectives were to survey the websites offering access to Quranic texts on their structure and linkages, and to propose a system design for retrieving Quranic text. A total of 125 websites offering access to Quranic texts were examined. Findings revealed that the websites offer texts and translation, recitation, excerpt of exegesis, and link to other websites consisting of news, event and related topics. A standard structure was not implemented by these website. the proposed system design focuses on texts, translation, recitation, exegesis, al-Hadith, its topics and themes like stories of of the prophets and places mentioned in al-Quran, and search feature.